Environmental Concern and Environmental Tax Awareness in Shaping Public Acceptance of Carbon Tax - Muhammad Ilmi; Grimonia Pertiwi; Gabriella Debora; Agya Larasati; Agung Budi (Jurnal Inovasi Pajak Indonesia, 2025)
Purpose — This study aims to examine the direct and indirect effects of environmental concern and environmental tax awarenesson public acceptance of carbon tax, emphasizing the interaction between affective and cognitive determinants.Design/methodology/approach — A quantitative approach is employed using a cross-sectional survey design. Data were collectedfrom 61 respondents and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to test direct andmediating relationships among constructs.Findings — The results reveal that environmental concern positively influences public acceptance of carbon tax but negativelyaffects environmental tax awareness, indicating a gap between pro-environmental attitudes and policy understanding. Furthermore,environmental tax awareness has a significant negative effect on public acceptance, suggesting that increased knowledge may leadto more critical evaluation of policy fairness and economic burden. However, mediation analysis shows that environmental taxawareness significantly mediates the relationship between environmental concern and public acceptance, highlighting its role as acognitive bridge in translating environmental values into policy support.Originality/value — This study contributes to the literature by integrating the Theory of Planned Behavior (TPB) and Value-Belief-Norm (VBN) theory within a dual-path framework, offering a nuanced understanding of how affective and cognitive factorsinteract in shaping public acceptance of carbon tax.Practical implications — The findings suggest that policymakers should prioritize transparent communication, equitable policydesign, and public education to enhance trust and social legitimacy of carbon taxation.